Collaborating a Dependent Business Model: Corporate Social Responsibility - Evidence from India - Sharma, Kriti; Gautam, Tara Prasad (Journal of Productive Discourse, 2024)
The research concludes that businesses in developing nations, notably India, exhibit a steadfast commitment to Corporate Social Responsibility (CSR). Despite marked advancements in CSR procedures, there remains a judgment for businesses to transcend self-interest and embrace a broader societal perspective. For multinational corporations (MNCs), robust CSR practices are indispensable for upholding their reputational integrity. The research utilizes secondary data of the Net Profit after taxes, CSR Spending and Budget for the Fiscal Years 2017–18 to 2021–22, Share prices for the fiscal years 2017–18 through 2021–22 on the BSE and NSE, and Sector-wise distribution of CSR initiatives from company websites, online databases, and annual reports. The findings suggest that businesses in developing nations, including India, are committed to CSR. While there has been an improvement in CSR practices, businesses are still not consistently going above and beyond or solely focusing on themselves. This study contributes valuable insights into the evolving CSR terrain within India, shedding light on the strides made and the persistent challenges encountered in fostering a symbiotic relationship between corporate profitability and social responsibility. By delineating these nuances, the research seeks to inform stakeholders and policymakers about the trajectory of CSR evolution, thereby fostering a conducive environment for sustainable and responsible business practices. The study provides valuable insights into the CSR landscape in India and the ongoing efforts to integrate responsible business practices.